Influence Factors Utilization of Family Planning Services among Reproductive Age Women’s in Primary Health Care (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Family planning services as an essential component of primary health care and reproductivehealth, contributes to reducing maternal and newborn mortality and morbidity and transmission of HIV.Attitudes and knowledge towards family planning services are role play and consider influence factors onfamily planning services, assess to the means of fertility regulation and communication between husbandand wife about desired family size and timing of pregnancy are essential for family planning.Objective: To determine the influence factors on family planning services of women in reproductive age.Also to determine the association between influence factors of family planning of women in reproductiveage and their demographic characteristic.Materials of the Study: The study design a quantitative research by descriptive study, the sampling it isnon-Probability “purposive” sample was a conducted on 150 females which attended with requirementhealth care services attained in primary health care centers at AL-Najaf city for period from September 7,2018 to February 16, 2018 November. A questionnaire it has used as a tool of data collection to fulfill thestudy. A descriptive and inferential statistics was used to analyze the data.Results: The study results indicate that the majority of study responses are age (30_37)years with 42.0%,duration marriage the most study sample (6_11)years with 44.0%. Related to number of children more halfstudy sample (3_5) with 49.3%, Level of education most are higher secondary school with 28.0%,Occupationthe majority study sample homemaker with 70.7% and live in urban. The study sample utilization of met family planning was oral contraceptive pills with 34.7%.In addition, the study sample are more than halftheir knowledge are poor and attitude negative about family planning. Conclusion: The majority of the sample study used contraceptive pills and IUD due easy and do not needto procedures and knowledge. There is a significant relationship between knowledge, attitude and items offamily planning. Some of demographic data effect upon knowledge and attitude because different in levelof education and residence.